Somatic traits and motor skill abilities in top-class professional speed climbers compared to recreational climbers - Krawczyk, M.; Ozimek, M. (Journal of Kinesiology and Exercise Sciences, 2014)
Aim of the study. To determine the basic parameters of speed climbers` somatic constitution and to determine whether high levels of strength and speed capability characterise top-class speed climbers. Material and methods. The study examined 5 competitors holding top positions in the Polish Mountaineering Association peed climbing ranking (during the 2009 season). The control group consisted of 10 recreational climbers. Measurements were taken of height, body mass, upper limb length and percentage level of fat; then, Body Mass Index was calculated. Strength ability was measured using dynamometric tests of the maximal local static strength of upper limbs. The following tests were used to determine the level of motor ability in subjects (standing broad jump, envelope run, sit-ups, sit and reach and spread sit, as well as a test for the maximum rate of movement of upper limbs). Maximal anaerobic work (MAW) was calculated. Results. It was established that the best competitors in speed climbing have significantly higher levels of explosive strength and maximal anaerobic work, better muscle mobilisation ability, and higher torso strength and endurance. Clear but statistically insignificant differences between the groups were observed in strength tests and flexibility. Both professional and recreational climbers presented similar levels of the somatic traits studied. Conclusions. High standards in speed climbing are connected with higher levels of speed capability. The scale of differences is a proof of the importance of speed capability in speed climbing. The importance of high upper limb muscle strength in climbing was confirmed. Amongst the somatic traits studied, only body mass can be treated as influencing the results in speed climbing.